Quadruple Helix of Entrepreneurship and Management Education - Miroslav REBERNIK (Revista de Management Comparat International)
This paper discusses the case of the entrepreneurship programme at the Faculty of Business and Economics at the University of Maribor, where academics, entrepreneurs, and managers have joined forces to develop effective entrepreneurship education and training that stimulates creativity and innovation among students. The underlying philosophy of the programme is twofold. First, education for future entrepreneurs and managers of smaller companies, characterized by the despecialization of job tasks, resource scarcity, and self-employment, must differ from management education for larger companies, where task specialization can take place. Second, during their studies, students should improve their creativity, develop ability for recognize opportunity, gain confidence, and acquire practical managerial experience. Classroom experience itself is not sufficient for developing students’ understanding of the value of innovation and creativity; rather, it should be upgraded through direct experience supported by real-life cases and role models. The discussion introduces the term quadruple helix of entrepreneurship education to stress the importance of four main players in such education: students, professors, entrepreneurs, and the supportive infrastructure of the entrepreneurship ecosystem.